Intestinal microbiota profiles in a genetic model of colon tumorigenesis correlates with colon cancer biomarkers - Francesco Vitali; Katia Tortora; Monica Di Paola; Gianluca Bartolucci; Marta Menicatti; Carlotta De Filippo; Giovanna Caderni (Scientific Reports, 2022)
Abstract Faecal (FM) and colon mucosal associated microbiota (MAM) were studied in a model of colorectal cancer (CRC), the Apc-mutated Pirc rats, and in age-paired wt F344 rats. Principal Coordinates Analysis indicated that samples’ distribution was driven by age, with samples of young rats (1 month old; without tumours) separated from older ones (11-month-old; bearing tumours). Diversity analysis showed significant differences between FM and MAM in older Pirc rats, and between MAM of both Pirc and wt rats and the tumour microbiota, enriched in Enterococcus, Escherichia/Shigella, Proteus and Bifidobacteriaceae. In young animals, Pirc FM was enriched in the genus Delftia, while wt FM was enriched in Lactobacillus and Streptococcus. Some CRC biomarkers and faecal short chain fatty acids (SCFAs) were also measured. Colon proliferation and DClK1 expression, a pro-survival mucosal marker, were higher in Pirc than in wt rats, while the mucin MUC2, was lower in Pirc rats. Branched SCFAs were higher in Pirc than in wt animals. By Spearman analysis CRC biomarkers correlated with FM (in both young and old rats) and with MAM (in young rats), suggesting a specific relationship between the gut microbiota profile and these functional mucosal parameters deserving further investigation.